Influence of RbF post deposition treatment on heterojunction and grain boundaries in high efficient (21.1%) Cu(In, Ga)Se2 solar cells. (June 2019) - Raghuwanshi, Mohit; Vilalta-Clemente, Arantxa; Castro, Celia; Duguay, Sébastien; Cadel, Emmanuel; Jackson, Philip; Hariskos, Dimitrios; Witte, Wolfram; Pareige, Philippe
Abstract: Post deposition treatments (PDT) by alkali fluorides applied to chalcopyrite-based absorbers have produced record efficiencies in thin-film solar devices in the past few years and recently the efficiency of 22.6% was achieved with Cu(In, Ga)Se2 (CIGS) using rubidium fluoride (RbF) PDT. However, the effects of RbF-PDT towards changes in its interfacial and grain boundary (GB) properties are still not fully understood. In this work, cells with efficiency higher than 21% are investigated by combination of atom probe tomography (APT) and transmission electron microscopy (TEM) to show how changes in GB and interface chemistry may facilitate high efficiencies. APT studies, carried out at the interface between CIGS absorber and solution-grown CdS buffer layer, show In enrichment and Cu depletion along with traces of Rb. Our APT studies reveal higher amounts of Rb (1.5 at. %) and lower amounts of Na and K (<0.5 at. %) at GBs as compared with previous studies (on non-PDT samples) thus indicating substitution of Na and K by Rb. However, concentration of all alkali elements inside the grain bulk is below detection limit of APT. The concentration of Rb at the GBs in CIGS is measured depth-dependent using both APT and TEM, which consistently shows the increase in Rb towards the Mo back contact. In addition, a pronounced Cu depletion is observed at the GBs which might enhance hole-barrier properties of the GBs, thus improving charge carrier collection and hence the overall efficiency of the device. Thus, understanding effects of RbF-PDT at the atomic scale provides new insights concerning the further improvement of CIGS absorber and interfaces. Graphical abstract: Image 1 Highlights: Characterization of heterojunction and grain boundaries in high efficient (21.1%) CIGS using TEM and APT. Rb is detected at CdS/CIGS heterojunction and indicates formation of RbInSe2 . Pronounced depletion in Cu at grain boundaries is observed which implies reduced recombination at grain boundaries. Both APT and TEM confirm increment in Rb grain boundary concentration towards Mo back contact. Rb replaces significant amount of Na and K from grain boundaries.